Efficacy and Safety of Vaccines After Conventional Treatments for Survival of Gliomas: A Systematic Review and Meta-Analysis - Amanzadeh Jajin, Elnaz; Oraee Yazdani, Saeed; Zali, Alireza; Esmaeili, Abolghasem (Oncology Reviews, 2024)
Background: Malignant gliomas are known with poor prognosis and low rate of survival among brain tumors. Resection surgery is followed by chemotherapy and radiotherapy in treatment of gliomas which is known as the conventional treatment. However, this treatment method results in low survival rate. Vaccination has been suggested as a type of immunotherapy to increase survival rate of glioma patients. Different types of vaccines have been developed that are mainly classified in two groups including peptide vaccines and cell-based vaccines. However, there are still conflicts about which type of vaccines is more efficient for malignant glioma treatment. Methods: Phase Ⅰ/Ⅱ clinical trials which compared the efficacy and safety of various vaccines with conventional treatments were searched in databases through November 2022. Overall survival (OS) rate, progression free survival (PFS), and OS duration were used for calculation of pooled risk ratio (RR). In addition, fatigue, headache, nausea, diarrhea, and flu-like syndrome were used for evaluating the safety of vaccines therapy in glioma patients. Results: A total of twelve articles were included in the present meta-analysis. Comparison of OS rate between vaccinated groups and control groups who underwent only conventional treatments showed a significant increase in OS rate in vaccinated patients (I2 = 0%, RR = 11.17, 95% CI: 2.460–50.225). PFS rate was better in vaccinated glioma patients (I2 = 83%, RR = 2.87, 95% CI: 1.63–5.03). Assessment of safety demonstrated that skin reaction (I2 = 0.0%, RR = 3.654; 95% CI: 1.711–7.801, p-value = 0.0058) and flu-like syndrome were significantly more frequent adverse effects win vaccinated groups compared to the control group. Subgroup analysis also showed that vaccination leads to better OS duration in recurrent gliomas than primary gliomas, and in LGG than HGG (p-value = 0). On the other hand, personalized vaccines showed better OS duration than non-personalized vaccines (p-value = 0). Conclusion: Vaccination is a type of immunotherapy which shows promising efficacy in treatment of malignant glioma patients in terms of OS, PFS and duration of survival. In addition, AFTV, peptide, and dendritic cell-based vaccines are among the most efficient vaccines for gliomas. Personalized vaccines also showed considerable efficacy for glioma treatments.